2008
DOI: 10.1590/s1516-18462008000200017
|View full text |Cite
|
Sign up to set email alerts
|

Amamentação no alojamento conjunto

Abstract: OBJETIVO: avaliar a amamentação em bebês do Alojamento Conjunto, identificar e avaliar as dificuldades no início do aleitamento materno. MÉTODOS: estudo transversal descritivo. A amostra foi constituída de 100 binômios mãe/recém-nascidos, em maternidade pública estadual que atende ao parto de alto risco pelo Sistema Único de Saúde. Utilizando protocolo do Fundo das Nações Unidas para Infância para observação e avaliação da mamada, foram registrados os comportamentos de cada dupla, computando-se a freqüência de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1
15

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 13 publications
1
5
1
15
Order By: Relevance
“…It is known that the function of sucking has great influence in breastfeeding 12,[21][22][23] . In clinical practice, one of the difficulties found by professional is the lack of an instrument that will aid them in the assessment of term babies' sucking 24 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the function of sucking has great influence in breastfeeding 12,[21][22][23] . In clinical practice, one of the difficulties found by professional is the lack of an instrument that will aid them in the assessment of term babies' sucking 24 .…”
Section: Resultsmentioning
confidence: 99%
“…In spite of the different forms of result interpretations, 20 to 60% of the pairs had initial difficulties in breastfeeding: sucking adequacy, bad body posture of mother and infant during feeding; anatomy aspect of the breasts, the pairs' responses and bonding. The difficulties were related to surgical delivery [12][13][14] and to the mother not having received previous information about breastfeeding 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Através dele consegue-se suprir todas as necessidades nutritivas do recém-nascido, além de reforçar o aumento de anticorpos, ganho de peso, propiciar maior vínculo entre mãe e filho, e promover o desenvolvimento das estruturas orais, que são responsáveis pelo funcionamento adequado da respiração, da sucção, da deglutição, da mastigação e da fala (1) . O alojamento conjunto é um sistema hospitalar em que o recém-nascido sadio permanece ao lado da mãe até a alta (2) . Tem por objetivo a integração mãe-bebê, contribuindo para o incentivo do aleitamento materno, orientações de cuidado da mãe com o bebê e a prevenção de infecções (3) .…”
Section: Introductionunclassified
“…The level of education is one of the factors that can interfere with difficulty breastfeeding. The literature states that this variable maternal education is correlated with early weaning, so the bigger the mother's education time duration of breastfeeding, demonstrating that cultural aspects that start in the context of maternal and child relationship extend to family and the community 16 . Escobar et al conducted a study in the emergency room of the Children's Institute in 1998 with a sample of 599 children and their parents, which found that 75,9% of mothers stopped breastfeeding without medical advice.…”
Section: Discussionmentioning
confidence: 99%